Comprehensive evaluation of icewine aroma quality based on ROAV and PCA-TOPSIS method - ZHANG Yang, QU Yilin, SUN Yongde, KONG Weifu, LI Hongjuan (Zhongguo niangzao)
Using 4 representative domestic icewines (numbered No.1-No.4) as research subjects, the volatile aroma components in the icewines were determined using headspace solid-phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS). The aroma quality of icewines was analyzed and evaluated by constructing principal component analysis (PCA)-technique for order preference by similarity to ideal solution (TOPSIS) model. The results showed that a total of 118 volative aroma components were detected in the 4 icewines, including 18 fatty acid ethyl esters, 8 acetate esters, 24 other esters, 13 alcohols, 12 terpenes, 4 norisoprenoids, 5 acids, 9 aldehydes and ketones, 15 aromatic compounds, and 10 other compounds. The aroma composition and content of 4 icewines exhibited significant differences. 22 important aroma compounds (ROAV>0.1) and 10 key aroma compounds (ROAV>1) were selected through the relative odor activity value (ROAV). The correlation results showed that ethyl octanoate showed a significant negative correlation with phenylacetaldehyde (P<0.05) and an extremely significant negative correlation with damascone (P<0.01), while damascone showed a significantly positive correlation with phenylacetaldehyde (P<0.05) and extremely significant negative correlations with decanoic acid ethyl ester and ethyl caprate (P<0.01). According to PCA-TOPSIS, the aroma evaluation results for 4 icewines, ranked in descending order of Si (relative closeness), were 0.804 (No.4), 0.572 (No.2), 0.411 (No.1), and 0.229 (No.3), indicating that icewine No.4 had the optimal aroma quality.